2021
DOI: 10.5114/pedm.2021.107720
|View full text |Cite
|
Sign up to set email alerts
|

Early functional and metabolic disorders in children with type I diabetes mellitus and diabetic nephropathy

Abstract: Type 1 diabetes (T1D) is mainly a disease of children and young adults. The onset of disease is associated with 3 classical symptoms: polydipsia, polyphagia, and polyuria. Hyperglycaemia is the main and primary metabolic disorder in T1D. One of the complications developing as a result of microangiopathy is diabetic nephropathy (DN). Additionally, diabetes remains the most common reason for progressing to end-stage renal disease (ESRD). The aim of the study was to evaluate the most initial metabolic and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…We speculate that cluster I in the T1D group, characterized by somewhat of an increase in PLT, hyperfiltration and reduced anti-apoptotic defense should be considered as a potential risk group for further complications, including DN and cardiovascular events. Previously, we have shown that children with T1D have increased GFR ( 28 ). This finding is in line with other research showing that a 25-50% elevation in the GFR is seen early in the course in up to one-half of patients with T1D, an abnormality that is exaggerated after ingestion of a protein load.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that cluster I in the T1D group, characterized by somewhat of an increase in PLT, hyperfiltration and reduced anti-apoptotic defense should be considered as a potential risk group for further complications, including DN and cardiovascular events. Previously, we have shown that children with T1D have increased GFR ( 28 ). This finding is in line with other research showing that a 25-50% elevation in the GFR is seen early in the course in up to one-half of patients with T1D, an abnormality that is exaggerated after ingestion of a protein load.…”
Section: Discussionmentioning
confidence: 99%
“…However, ET‐1 levels were shown to be considerably greater in T1D patients than in healthy children in research by Burlaka Ievgeniia et al on children with T1D and DKD during a 6‐year period. ET‐1 levels were higher in the DKD group compared to the T1D group and were positively correlated with disease duration in children with DKD (Burlaka & Maidannyk, 2021). However, the most recent study, which excluded patients with other forms of diabetes and employed T1D patients and healthy people as controls for each other, discovered that ET‐1 appeared to be lower in the T1D group compared to the control group (Alkaabi et al, 2011).…”
Section: Correlation Of Et‐1 Levels With Dkdmentioning
confidence: 99%
“…Interestingly, a group of children with diabetic nephropathy and coexisting type 1 diabetes participating in the Burlaka and Maidannyk study showed higher blood cholesterol levels and higher systolic and diastolic blood pressure values than children with type 1 diabetes without signs of nephropathy. Consequently, lipid disorders may be one of the factors that affect the kidney vasculature and blood pressure ( 117 ). In contrast, other studies have observed a reduced prevalence of micro/macroalbuminuria in obese children with T1D compared to those with healthy weight.…”
Section: Obesity As a Factor Of Developing T1d Vascular Complicationsmentioning
confidence: 99%